Pengaruh Corporate Social Responsibility (Diversity, Employee Support, dan Environment) Terhadap Employee Performance Bank BRI Kantor Cabang Surabaya Pahlawan - Adhistamala, Adhistamala; Pratiwi, Ni Made; Mulyati, Awin (Jurnal Dinamika Administrasi Bisnis, 2021)
Good corporate governance in the implementation of Corporate Social Responsibility to be realized in the fulfillment of human rights whose results can be directly enjoyed by employees. To facilitate data collection, techniques are needed in making questionnaires that will be distributed to respondents. In this study, the data collection technique used is through a questionnaire using a Likert Scale which is a psychometric scale in the research questionnaire. The regression coefficient of the negative value Diversity variable states that there is no significant increase in employee performance through the variable Diversity. The regression coefficient for the Employee Support variable is positive, stating that there is a significant increase in Employee Performance through the variable Employee Support. The positive Environment variable regression coefficient states that there is a significant increase in Employee Performance through the variable Environment. The results of this study indicate that the three independent variables have an influence on the dependent variable if tested simultaneously, but one of the three variables doesn’t have a strong influence, namely the Diversity variable.Keywords: Corporate Social Responsibility Diversity, Employee Support, Environment, Employee Performance.